THE EFFECT OF THE TEAM GAMES TOURNAMENT LEARNING MODEL ON STUDENTS' COLLABORATION SKILLS IN GEOGRAPHY SUBJECTS AT SMA NEGERI 10 PEKANBARU - Elfira Zulfani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to determine the Influence of the Team Games Tournament Learning Model on Students' Collaboration Ability in Geography Subjects. This study uses a quantitative approach with the Quasi Experimental method with a pretest-posttest control group design. The population in this study is grade XI students consisting of 4 classes. The sampling technique used Cluster Sampling, with class XI.4 as the control class and class XI.3 as the experimental class by providing the treatment of the Team Games Tournament learning model. Data collection was carried out by pre test and post test to see students' collaboration skills, complemented by observation and documentation. The data analysis in this study used parametric statistics with the T-Test test. The results of this study show that the Team Games Tournament learning model affects students' collaboration skills in the geography subject of Disaster Mitigation and Adaptation. The average increase in students' collaboration ability (pre test and post test) results in the experimental class was higher than in the control class, with the average comparison of the collaboration ability of students in the experimental class of 56.50 increasing to 62.35 with a percentage increase of 5.85%. Meanwhile, the average control class score of 48.98 increased to 51.23 with a percentage increase of 2.25%. Based on the results of the t-test hypothesis, a Sig.(2-tailed) value of 0.000 is obtained, then according to the basis for decision-making in the Independent Sample T-Test, if the sig < 0.05 (0.000 < 0.05) or ttable > ttable (5,518 > 1.664), if the ttable is > ttable, then Ho is rejected or Ha is accepted. Based on the explanation above, it can be seen that there is a significant influence of the Team Game Tournament learning model on students' collaboration abilities in Geography subjects at SMA Negeri 10 Pekanbaru.